Corporate environmental responsibility and bank loans. Issue 3 (29th May 2022) - Cai, Li; He, Chaohua
Abstract: Drawing on both qualitative analyses of banks' sustainability reports and quantitative analyses of 11, 538 bank loans from 1993 to 2018, we explore interactions between corporate environmental responsibility (CER) and bank loan contracting. We find CER dominates how corporate social responsibility (CSR) affects bank loans. We propose a two‐way relationship between CER and bank loans. Firms with strong CER performance receive cheaper bank loans due to banks' environmental risk management efforts. These banks provide services to corporate borrowers that have a positive influence on borrowers' ongoing environmental performance.